Anisotropic Adhesion: Exploiting Supramolecular Interactions from Polymeric Colloids for Strong Anisotropic Adhesion between Solid Surfaces (Adv. Mater. 14/2020). Issue 14 (7th April 2020) - Tardy, Blaise L.; Richardson, Joseph J.; Greca, Luiz G.; Guo, Junling; Ejima, Hirotaka; Rojas, Orlando J.
Abstract : In article number 1906886, Blaise L. Tardy, Hirotaka Ejima, Orlando J. Rojas, and co‐workers describe the controlled organization of strong polymeric colloids into outstanding biomimetic adhesives with multiscaled architectures. While the adhesive possesses the attributes of conventional structural adhesives, with strength comparable to those commercially available, a direction‐dependent adhesive strength diverging by more than 70‐fold is reported. Image credit: Luiz Greca.